2020
DOI: 10.1021/acsphotonics.0c00189
|View full text |Cite
|
Sign up to set email alerts
|

Strong Optical Feedback Stabilized Quantum Cascade Laser

Abstract: A narrow-line-width quantum cascade laser (QCL) is highly demanded for high-resolution spectroscopy of narrow molecule absorption lines. This work shows a low-noise QCL stabilized by strong optical feedback without any feedback phase control. Although optical feedback is usually detrimental to the stability of laser diodes, the QCL is highly stable against optical feedback. The stabilized QCL line width is proved to be insensitive to the feedback phase, as long as the feedback strength is strong enough. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…This is in contrast to QCLs, where the chaotic LFFs mostly occur at near-threshold currents 22 25 . Our previous work has shown that QCLs operated far above the threshold were much more stable 80 , 81 . When the ICL is pumped at 105 mA with an output power of 1.7 mW, both the bifurcation diagram in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This is in contrast to QCLs, where the chaotic LFFs mostly occur at near-threshold currents 22 25 . Our previous work has shown that QCLs operated far above the threshold were much more stable 80 , 81 . When the ICL is pumped at 105 mA with an output power of 1.7 mW, both the bifurcation diagram in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure 1b, the free-running QCL exhibits a lasing threshold of 245 mA and emits a single mode around 2210/cm or 4.53 µm (see inset). The optical linewidth is extracted from the analysis of the measured frequency noise spectrum [16]. Figure 1c shows that the optical linewidth is around 16 MHz.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…The slight increase in the linewidth with the pump current can be attributed to the non-uniform carrier distribution induced by the spatial hole-burning effect [34,35]. On the other hand, the small fluctuations of the linewidth at 270 mA and 290 MA are due to the fact that the operation temperature is slightly tuned at each pump current to meet the frequency requirement of the frequency discriminator [16,36].…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is relevant to note that EOF does not always lead to destabilization and is of utter interest for controlling the semiconductor laser properties. For instance, it is possible to tune and stabilize the linewidth of lasers by applying a strong optical feedback [48][49][50][51]. However, EOF can also have some downside effects in the case destabilization is the most dominant phenomenon, generally for high feedback strengths.…”
Section: Dynamical Regimesmentioning
confidence: 99%